Pharyngocutaneous Fistula- Frequency and Risk Factors - Sattar, Md Abdus; Uddin, Md Mosleh; Salam, Kazi Shameemus; Razib, Syed Farhan Ali; Uddin, Md Momin; Hossain, Delwar; Siddiquee, Belayat Hossain (Bangladesh Journal of Otorhinolaryngology, 2019)
Setting: Study was conducted in the Department of Otolaryngology and Head-Neck surgery of Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh from 2006 to 2017. Objectives: To find out the frequency, risk factors, and its effect on the management of pharyngocutaneous fistula (PCF). Methods: Observational, Cross Sectional study. Number of laryngectomized patients 249. Results: Total PCF developed 48 (19.27%). Irradiated patients with multiple co-morbidities had more chance to develop PCF. Conclusion: High incidence of pharyngocutaneous fistula mostly due to advanced stage of disease, various levels of surgical expertise and post irradiated patients with multiple comorbidities. Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 156-161